1995
DOI: 10.1172/jci118275
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Pseudomonas aeruginosa gene products stimulate respiratory epithelial cells to produce interleukin-8.

Abstract: Respiratory epithelial cells play a crucial role in the inflammatory response during Pseudomonas aeruginosa infec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
305
4
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(321 citation statements)
references
References 39 publications
11
305
4
1
Order By: Relevance
“…L, airway lumen; SG, submucosal glands. lin) (17), and PAO͞NP (deficient in production of pilin) (13). That these media were as potent as that of wild type essentially excluded a role for the mutant gene products (data not shown).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…L, airway lumen; SG, submucosal glands. lin) (17), and PAO͞NP (deficient in production of pilin) (13). That these media were as potent as that of wild type essentially excluded a role for the mutant gene products (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…We next addressed the question of which components of P. aeruginosa are responsible for MUC 2 up-regulation. Via the screening of P. aeruginosa mutants, it has been found that diverse products of this organism can affect host gene expression (13). We assessed the role of some of these in MUC 2 up-regulation by testing the potency of culture supernatant from bacterial mutants PAOR1 (deficient in production of the P. aeruginosa autoinducer, elastase, alkaline protease, and neuraminidase) (14-16), AK1152 (deficient in production of pilin and flagel- FIG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secretion of IL-8, TNF-and other proinflammatory cytokines by airway epithelial cells and lung macrophages with accumulation and activation of neutrophils in the CF airways may underlie the early pathogenesis of CF lung disease [58,59,63,64]. This inflammatory process is greatly magnified by epithelial cell IL-8 production stimulated by products of colonizing bacterial pathogens and neutrophils [65,66]. Bonfield et al reported a selective reduction in IL-10 production by CF bronchial epithelial cells and reduced IL-10 levels in CF bronchoalveolar lavage fluid [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Persistent bacterial colonisation, specifically by Pseudomonas aeruginosa (PA), is a characteristic feature of the CF lung, and may be the primary stimulus for neutrophil infiltration. 4 Thus, PA infection has been shown directly to stimulate secretion of the pro-inflammatory cytokine interleukin-8 (IL-8), a major neutrophil chemoattractant, in the airways, 5 which is produced by several cell types, including epithelial cells. Recently we have shown, that the degree of IL-8 stimulation in primary airway epithelial cells is directly related to the number of PA bound to the cell surface.…”
Section: Introductionmentioning
confidence: 99%